Guillain-Barré Syndrome in Nepalese Children - Bhattarai, P; Shrestha, PN; Sharma, A (Journal of Institute of Medicine Nepal, 2009)
Background: Guillain-Barré Syndrome (GBS) is a group of autoimmune syndromes consisting of demyelinating and acute axonal degenerating forms of the disease. This study gives the profile of 30 patients who were admitted with the diagnosis of GBS in a pediatric hospital. Methods and material: We reviewed the admitted case notes of children admitted with the diagnosis of GB syndrome from January 2005 to December 2007. The data were analyzed to find out the demographic features, preceding illness, clinical features and CSF findings. Result: The age ranged from 3.6 years to 14 years. The mean (SD) age was 4.9 (9.7) years. The most common symptoms were inability to walk after awaking in the morning. The median evolving time from the onset of illness to nadir was 12 days. The CSF protein concentration ranged from 60 to <100mg% and the CSF cell counts were less than 10/cmm in 23 patients and 11-19 in 7 patients. Conclusion: We could not find any previous study done in such a large paediatric population of this country. Our results show the similarity in pattern of age distribution, preceding events, and cell protein dissociation similar to that of other studies. Keywords: Guillain-Barré Syndrome, diagnostic criteria, children, clinical profile, hospital. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 31-33